2015
DOI: 10.1016/j.bjorl.2014.10.003
|View full text |Cite
|
Sign up to set email alerts
|

Performance of hearing skills in children with auditory neuropathy spectrum disorder using cochlear implant: a systematic review

Abstract: The analyzed studies demonstrated that after cochlear implant surgery, individuals with auditory neuropathy spectrum disorder improved their performance of hearing skills and had similar performance to that of children with sensorineural hearing loss using cochlear implant.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
9
1
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 31 publications
(101 reference statements)
3
9
1
1
Order By: Relevance
“…In Pereira et al (14) , there was a lower number of teaching exposure until reaching the correct responses criteria and a synthesis of researches revealed that children with neurosensory hearing loss and CI present few repetitions to teaching blocks to learn listener's behaviors, such as to relate pictures to dictated stimuli (25) . However, this high quantity of repetitions to the teaching blocks was also found in the study case with ANSD and CI 6 and suggests some hypothesis. The participants' performance in both studies can indicate a behavioral evidence of auditory dyssynchrony caused by ANSD and confirms the findings of the Audiology about the difficulties on the acquisition and maintenance of listen abilities, what turns the auditory rehabilitation of this public a challenge (5,6) .…”
Section: Discussionsupporting
confidence: 68%
See 3 more Smart Citations
“…In Pereira et al (14) , there was a lower number of teaching exposure until reaching the correct responses criteria and a synthesis of researches revealed that children with neurosensory hearing loss and CI present few repetitions to teaching blocks to learn listener's behaviors, such as to relate pictures to dictated stimuli (25) . However, this high quantity of repetitions to the teaching blocks was also found in the study case with ANSD and CI 6 and suggests some hypothesis. The participants' performance in both studies can indicate a behavioral evidence of auditory dyssynchrony caused by ANSD and confirms the findings of the Audiology about the difficulties on the acquisition and maintenance of listen abilities, what turns the auditory rehabilitation of this public a challenge (5,6) .…”
Section: Discussionsupporting
confidence: 68%
“…However, this high quantity of repetitions to the teaching blocks was also found in the study case with ANSD and CI 6 and suggests some hypothesis. The participants' performance in both studies can indicate a behavioral evidence of auditory dyssynchrony caused by ANSD and confirms the findings of the Audiology about the difficulties on the acquisition and maintenance of listen abilities, what turns the auditory rehabilitation of this public a challenge (5,6) . On the other hand, some procedure adjustments can be adopted at MEI teaching viewing at minimizing the auditory dyssynchrony and the discrepancy between the listening and speaking behaviors (measured by the correct response percentages quite distinct for the same words).…”
Section: Discussionsupporting
confidence: 68%
See 2 more Smart Citations
“…Although there is research that demonstrates the effectiveness of CI for people with ANSD regarding improvement of auditory performance -as reflected in the bibliographical review, 28 there is no consensus between studies on how and when a child with ANSD presents good development. Currently, research that demonstrates detailed results that compose what is considered improvement auditory performance in children with ANSD is scarce.…”
Section: Discussionmentioning
confidence: 99%